Terebellidae (Annelida, Terebelliformia) from Lizard Island, Great Barrier Reef, Australia - Nogueira, João Miguel De Matos; Hutchings, Pat; Carrerette, Orlemir (Zootaxa, 2015)
In a survey of the polychaetes of the Lizard Island region, sixteen new species of terebellids, plus one previously described species, were found from material collected during the two week long Lizard Island Taxonomic Workshop in 2013, along with material collected from previous projects carried out at Lizard Island. This included the CReefs Project (http://www.aims.gov.au/creefs/field-program.html), of which Lizard was one of the nodes. Those species are distributed as follows: one species of each of the following genera Eupolymnia Verrill, 1900, Lanice Malmgren, 1866; Lanicides Hessle, 1917, Lanicola Hartmann-Schröder, 1986, Pistella Hartmann-Schröder, 1996, Reteterebella Hartman, 1963, and Terebella Linnaeus, 1767; two species of Nicolea Malmgren, 1866; three species of Pista Malmgren, 1866 and four of Loimia Malmgren, 1866, together with another new species, belonging to the new genus Lizardia n. gen. Keys for identification of these genera and species are provided, together with generic diagnoses and full descriptions for all species; for each new species, comparisons with the morphologically most similar congeners are provided. A redescription of Reteterebella queenslandia Hartman, 1963 is also included.